Spells at the Cradle. The Magic of Words in Folk and Lyrical Lullabies - Stefaniak-Maślanka, Beata (Poznańskie Studia Slawistyczne, 2012)
The article focuses on some examples of magic in traditional folk lullabies and lyrical lullabies for children. The aforementioned types of genre should invoke child’s sleep by using special words or melody. On the other hand, traditional lullabies were used to protect children or bring them health and happiness. To accomplish this, the singer often called some „higher being” for help. In the article that kind of speech acts are considered as magical behavior. The second part of the text discusses use of language, character of content and some special procedures in lyrical lullabies, that can be called „magical”. This kind of magic is, however, created by lullaby authors, who practice it as an intentional method to „do things with words”.